Gaudeamus! Humorous Poems - Scheffel, Joseph Victor von, 1826-1886; Leland, Charles Godfrey, 1824-1903 (Salt Lake City, UT : Project Gutenberg, 2011)
"Gaudeamus! Humorous Poems" by Joseph Victor von Scheffel is a collection of humorous poetry written in the late 19th century. The book features a variety of whimsical poems, many of which draw on historical and geological themes, presenting a playful take on humanity's past and nature's quirks. The poems serve both as charming anecdotes and comedic stories, reflecting the light-hearted spirit of the author. At the start of the collection, the translator's preface gives insight into its purpose and background, emphasizing Scheffel's popularity in Germany and the enduring appeal of his playful wit. The opening poem, "Granite," introduces a geological character lamenting the current state of the world, while the subsequent pieces like "The Ichthyosaurus" and "The Tazzelworm" continue to blend humor with natural history, showcasing various prehistoric creatures in amusing scenarios. This opening portion establishes a tone of levity and cleverness, inviting readers to enjoy the rich, amusing exploration of both biological and cultural elements present throughout the work. (This is an automatically generated summary.)
Release date is 2011-04-13
Produced by Charles Bowen, from page scans provided by Google Books
Keywords: German poetry -- Translations into English; German wit and humor